THE OVERVIEW OF ENVIRONMENTAL SANITATION IN OSING CULTURAL TOURISM AREA: STUDI IN FIVE SUB-DISTRICTS IN BANYUWANGI REGENCY - Husni Abdul Gani (Program Studi Ilmu Keperawatan Universitas Jember, 2016)
Diarrhea is one major cause of morbidity and mortality in developing countries. In 2013, in the District Cermee Bondowoso determined extraordinary events diarrhea. Since the determined extraordinary events diarrhea, has never done research the factors re lated to the incidence of diarrhea. Objectives of this study to determine the factors re lated to the incidence of diarrhea, especially environmental sanitation, water supply, personal hygiene, food sanitation, the availability of latrines, and fecal waste behavior. This study was a cross-sectional, with sample of 105 patients diarrhea and technique simple random sampling. Result show that factors related to diarrhea include environ mental sanitation (p value = 0.000), water supply (p value = 0.005), personal hygiene (p